«MUZÍKA TEORIYASÍ» PÁNINDE «INTERVALLAR» TEMASÍN OQÍTÍWDA INTERAKTIV USÍLLLARDAN PAYDALANÍW - Tajetdinova, S.M.; Axetova, G.J. (SCIENCE and SOCIETY, 2025)
The article devoted to the use of interactive methods in teaching the subject of «music theory». The subjest «Intervals» was chosen as the object of research. The following interactive methods were used while studying the topic: «Associative row», «Find a mistake», «Islands». These interactive methods provide a faster and deeper understanding of the content of the topic «Intervals».